2015
DOI: 10.1111/nous.12091
|View full text |Cite
|
Sign up to set email alerts
|

On the Innocence and Determinacy of Plural Quantification

Abstract: Plural logic is widely assumed to have two important virtues: ontological innocence and determinacy. It is claimed to be innocent in the sense that it incurs no ontological commitments beyond those already incurred by the first‐order quantifiers. It is claimed to be determinate in the sense that it is immune to the threat of non‐standard (Henkin) interpretations that confronts higher‐order logics on their more traditional, set‐based semantics. We challenge both claims. Our challenge is based on a Henkin‐style … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…There is a parallel argument in Florio and Linnebo (2016). Florio and Linnebo are tentative but come close to biting the bullet:…”
Section: Jones's Commitment To Plural Realismmentioning
confidence: 99%
“…There is a parallel argument in Florio and Linnebo (2016). Florio and Linnebo are tentative but come close to biting the bullet:…”
Section: Jones's Commitment To Plural Realismmentioning
confidence: 99%
“…But this tacit assumption has recently been challenged by Florio and Linnebo (2016). According to their observation, besides Boolos's canonical semantics, there is another non-standard Henkin semantics for plural logic.…”
Section: Alternativementioning
confidence: 99%
“…14 Thanks to Mary Leng for suggesting this way of putting it.15 It is sometimes suggested that our grasp of plural logic will deliver the required combinatorial concept. But the same question arises: what allows us to grasp full plural logic, rather than Henkin plural logic?Florio and Linnebo (2016) develop this criticism elegantly.…”
mentioning
confidence: 99%